"A Rush and a Push and the Land Is Ours": Territorial Expansion, Land Policy, and U.S. State Formation. Issue 1 (23rd April 2014) - Frymer, Paul
<x content-type="archive" xml:space="preserve">Abstract</x> I examine the role of US land policy in strategically controlling and moving populations around the continent with the goal of expanding borders and securing and incorporating new territory on the frontier. The government effectively used land policies and population control to enable an otherwise constrained American state to assert authority over the direction of expansion, to engineer settlement patterns in a manner to secure the territory without a large military, and to maintain an official fidelity to constitutional principles while engineering a dominant racial vision. I examine both the success and failures of these policies over the nineteenth century, with material drawn from government documents and primary sources. I discuss the consequences of this land policy for how we understand the American state in the context of comparative state and racial formation.